Cu-Doped Sr2Fe1.5Mo0.5O6−δ as a highly active cathode for solid oxide electrolytic cells. Issue 55 (21st June 2019) - Xu, Chuming; Zhen, Shuying; Ren, Rongzheng; Chen, Haosen; Song, Weili; Wang, Zhenhua; Sun, Wang; Sun, Kening
Abstract : Perovskite oxide Sr2 Fe1.3 Cu0.2 Mo0.5 O6− δ (SFCM) is prepared and evaluated as a novel cathode material for solid oxide electrolytic cells (SOECs). Abstract : Perovskite oxide Sr2 Fe1.3 Cu0.2 Mo0.5 O6− δ (SFCM) is prepared and evaluated as a novel cathode material for solid oxide electrolytic cells (SOECs). At 750 °C, the interfacial polarization resistance value decreased from 1.834 to 1.125 Ω cm 2 and the SFCM cathode exhibited excellent stability for 100 h, without any significant attenuation, at an electrolytic voltage of 1.5 V.